Superalloys 2000 (Ninth International Symposium) 2000
DOI: 10.7449/2000/superalloys_2000_767_776
|View full text |Cite
|
Sign up to set email alerts
|

Topologically Close Packed Phases in an Experimental Rhenium-Containing Single Crystal Superalloy

Abstract: The kinetics, morphology and composition of the formation of TCP phases in an experimental alloy containing no tungsten is studied. At high temperature P phase forms after 20 h, whereas below 950°C the phases p and R occur. At lower temperatures a polycrystalline form of cr phase is observed which is meta-stable but acts as a nucleation site for the other phases. The phase occurrence and compositions are compared with a thermodynamic model using a rhenium-containing database, and reasonable agreement is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 13 publications
2
53
0
Order By: Relevance
“…Together with supplemental experiments in the temperature range around the incipient melting point, a consistent solution heat treatment temperature of 1340 °C was selected for all Astra-1 alloys as maximum temperature without partial melting. The required solution heat treatment time has been determined by the investigation of the segregation distribution coefficients k s after solution heat treatment times of 1,4,8,16,24 and 32 h at 1340 °C. For this purpose, EPMA analyses (electron probe microanalyzer JXA-8100, JEOL, Tokyo, Japan) of all elements were carried out by mappings of a 750x750 µm 2 area (measuring details can be found in [12]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with supplemental experiments in the temperature range around the incipient melting point, a consistent solution heat treatment temperature of 1340 °C was selected for all Astra-1 alloys as maximum temperature without partial melting. The required solution heat treatment time has been determined by the investigation of the segregation distribution coefficients k s after solution heat treatment times of 1,4,8,16,24 and 32 h at 1340 °C. For this purpose, EPMA analyses (electron probe microanalyzer JXA-8100, JEOL, Tokyo, Japan) of all elements were carried out by mappings of a 750x750 µm 2 area (measuring details can be found in [12]).…”
Section: Methodsmentioning
confidence: 99%
“…However, the addition of Re is limited by the highly increased susceptibility to form brittle and harming TCP-phases. To overcome this problem, the most recent alloy development led to the addition of Ru, which appears to be advantageous through microstructure stabilization with respect to TCP-formation [3][4][5][6][7][8][9][10][11]. However, additions of the elements Re and Ru also give rise to economic concerns, since both elements are short in availability and thus also fairly expensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the creep properties of superalloys containing high amounts of refractory elements decrease due to formation of the intermetallic topologically close-packed phases, known as TCP [1][2][3][4][5][6][7][8]. The TCP phases which were reported to be precipitated in single crystal superalloys are: σ (tetragonal, P 42/mnm), µ (trigonal, R-3m), P (orthorhombic, P nma) and R (rhombohedral, P -31m) phases [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the addition of rhenium plays an important role on high temperature creep resistance in single crystal nickel base superalloys [3,4] . However, Re has a strong segregation tendency in the γ phase, and homogenization of Re is very difficult even at the temperatures above 1300 for a long time ℃ , consequently the TCP phase which is harmful to mechanical properties may precipitate during long term high temperature service [5] . Moreover, Re is rare resource and very expensive element.…”
Section: Introductionmentioning
confidence: 99%